Morpho- physiological characterization of litchi ( Litchi chinensis sonn. ) in Wayanad - Sanjay D Chavaradar (Department of Pomology and Floriculture, 2016)
Litchi (Litchi chinensis Sonn.) is an important subtropical fruit crop of family Sapindaceae. Unlike in Northern India, it is grown as an off season crop in southern parts of the country due to which there is ample scope for commercialisation. Assessment of existing variability is a pre-requisite for taking up successful crop improvement programmes in the future. Thus, the present investigation entitled “Morpho-physiological characterization of litchi (Litchi chinensis Sonn.) in Wayanad” was taken up with the main objective of studying the flowering and fruit set pattern in litchi and the related morpho-physiological parameters under Wayanad situations of Kerala. A total of 32 collections maintained at farmers’ fields as well as RARS, Ambalavayal in Wayanad were evaluated. All the characters studied were found to be widely variable. Variation in tree characters include age (5-79 years), height (3 to 19 m), trunk girth (28 to 540 cm), crown shape (semi-circular, oblong, spherical, broadly pyramidal, and irregular), branching pattern (erect, opposite, verticillate, horizontal, and irregular), leaf blade shape (elliptic and lanceolate), leaf length (12 to 16.80 cm) and breadth (1.8 to 5.2 cm), young leaf colour (pinkish green, greenish yellow and light green), matured leaf colour (green, light green and dark green), shoot length (15 cm - 26 cm) and internodal length (2.8 cm – 5.2 cm). Principal component analysis (PCA) performed on the basis of tree characters revealed that the first two principal components (PCs) accounted for 77.3 per cent of the total variation with contributing characters such as tree age, height, trunk girth, leaf length, shoot length and internodal length. The clustering of the collections based on the PCA plot resulted in the formation of 9 clusters. Regarding flowering, only 26 collections flowered and flowering lasted for 12-35 days. Seventy five percent of the collections flowered in August to September whereas, 7.14 percent flowered in February to March. Flowering both in August to September and February to March was seen in 17.85 per cent of the collections. Days taken from flowering to fruit maturity ranged from 71 (Coll. 4) to 94 days (Coll. 30) while days from fruit set to maturity varied from 58 (Coll.10) to 75 days (Coll.2).PCA of phenological and inflorescence characters revealed that the first two PCs explained 86.4 per cent of total variation. Clustering of collections based on the above PCA resulted in formation of 5 clusters. The fruit varied in length, width and weight as 2.8 to 3.8 cm, 2.1 to 3.2 cm and 16.9 to 25.8 g, respectively. Majority of the collections had medium skinned fruits (80 %) and matured fruits were pinkish red to greenish yellow in colour. Aril weight ranged from 12.1 to 17.1 g, where 50 per cent of collections had medium, while, 25 per cent of each collections had thin and thick arils with seed weight (100 seeds) ranging from 210 to 297 g. The collections evaluated consisted of regular bearers (55 %) and alternate bearers (45 %) and the yield was recorded as ranging from one to 30 kg/plant. The fruits could be stored for 3 to 4 days. The first two components explained 71.9 per cent of variation. Clustering based on first two PCs grouped the collections into 7 distinct clusters. Physiological parameters, viz., chlorophyll (1.07 to 1.87 mg/g), cell sap pH (5.12 to 5.96), total carbohydrates (3.79 to 13.48 %) and C/N ratio (3.83 to 8.44) were recorded. The results of PCA read 75.6 percent of the total variation by the first two PCs. Clustering of physiological parameters based on first two PCs resulted in 8 clusters. Quality parameters viz., total sugar (10.18 to 15.50 %), TSS (15.10 to 19.6 0 B), acidity (0.38 to 1.18 %) and the TSS/acidity ratio (12.8 to 51.58) were recorded. The first three main PCs explained a total cumulative variance of 95.5 per cent. Based on the first two PCs, 7 clusters were formed. In the sensory evaluation based on nine point hedonic scale, Coll. 2 was found to be promising because of its flavour and taste. In the present investigation, Coll. 2, Coll. 10 and Coll. 13 were identified as superior types based on fruit size, weight, yield, quality and sensory parameters. Thus, these collections need to be evaluated to ascertain the stability under different regions which can be exploited in order to secure premium price for the crop. Further, studies are required to standardize the management practices including the eco physiological aspects of litchi for Kerala and promoting cultivation of this crop.